Remarkable Active Site Utilization in Edge‐Hosted‐N Doped Carbocatalysts for Fenton‐Like Reaction - Huajie Zhong; Zeyu Gong; Jiaxing Yu; Yu Hou; Yuan Tao; Qi Fu; Huangsheng Yang; Xinzhe Xiao; Xingzhong Cao; Junhui Wang; Gangfeng Ouyang (Advanced Science)
Abstract Improving the utilization of active sites in carbon catalysts is significant for various catalytic reactions, but still challenging, mainly due to the lack of strategies for controllable introduction of active dopants. Herein, a novel “Ar plasma etching‐NH3 annealing” strategy is developed to regulate the position of active N sites, while maintaining the same nitrogen species and contents. Theoretical and experimental results reveal that the edge‐hosted‐N doped carbon nanotubes (E‐N‐CNT), with only 0.29 at.% N content, show great affinity to peroxymonosulfate (PMS), and exhibit excellent Fenton‐like activity by generating singlet oxygen (1O2), which can reach as high as 410 times higher than the pristine CNT. The remarkable utilization of edge‐hosted nitrogen atom is further verified by the edge‐hosted‐N enriched carbocatalyst, which shows superior capability for 4‐chlorophenol degradation with a turnover frequency (TOF) value as high as 3.82 min−1, and the impressive TOF value can even surpass those of single‐atom catalysts. This work proposes a controllable position regulation of active sites to improve atom utilization, which provides a new insight into the design of excellent Fenton‐like catalysts with remarkable atom utilization efficiency.